RELATIONSHIP ATTITUDE AND NURSE KNOWLEDGE ABOUT THE COMPLIANCE OF THE USE OF PERSONAL PROTECTIVE EQUIPMENT (PPE) IN OUTPATIENT INSTALLATION AT TANGERANG SELATAN HOSPITAL - Muhamad Saleh Arifin; Hardiman SG; Suherman; Dihartawan (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
Results from the National Safety Council report show that the incidence of workplace accidents in hospitals is 41% higher compared to other industrial workers. Frequent cases are needle needles, scratches, and infectious diseases. The implementation of K3RS is of course determined by policy by the hospital by applicable laws and regulations. The purpose of this study was to see that there is a relationship between knowledge and attitudes with adherence to PPE use. This study used quantitative analysis methods with a cross-sectional study design. This study was conducted in November-January at South Tangerang Hospital. The population of this research source is all South Tangerang Hospital Workers, the target population is nurses at South Tangerang Hospital. The sample size of this study was 100 samples. Take samples using random sampling techniques. Analysis of research data using chi-square. Based on the analysis, it was found that all independent variables are related to dependent variables. Including, knowledge p-value 0.000 and attitude with p-value 0.000. It is estimated that the hospital will conduct routine socialization of the use of PPE for nurses. Nurses should be more compliant with the use of PPE.